"Producción de biomasa y determinación den índice de cosecha en genotipos de quinua (Chenopodium quinua willd), en la finca experimental la María - Pinargote Álava, John Jairo (2018)
The research was conducted on the Campus of the Finca Experimental "La Maria", belonging to the State Technical University of Quevedo, located in the 7,5 kilometer of the Quevedo - El Empalme, canton Mocache, province of Los Ríos. For which used twenty-one genotypes of quinoa (Chenopodium quinoa Willd.) in agro-climatic conditions of the area of Mocache, for a period of five months (august-december) in the year 2017, which were evaluated at 60 days after sowing and the reach physiological maturity. The objectives of the study were: determine the production, harvest index and biomass partitioning. Each experimental unit was prepared by a plot of 1 m2, a total of 63 plots separated equidistantly to 3 m between them, and these in turn formed, was implemented a completely random (DCA) with twenty-one treatments and three replications design for 20 plants each, which were distributed at a distance of 0,25 m x 0,30 m planting; the test of Tukey (p ≤ 0,05) was applied to the comparison of averages between treatments. Harvest index was statistically different (p ≤ 0,05), achieving highlight values above the T15, T18 and T3 with 0,56; 0,55 and 0,54 respectively. The lower results were recorded in the T7 and T20 with 0,06 and 0,24 respectively. The variable production of biomass showed significant statistical differences (p ≤ 0,05). The treatment increased biomass production obtained was the T13 with 347,45 grams per plant, while lower production was that of the T7 with 12,41 grams. These results demonstrate the feasibility of the production of quinoa in the central region of the Ecuador coast. Key words: Quinoa, Genotypes, Biomass, Partitioning, Harvest index